Perception crisis: Industrial architectural interventions to maintain perceptual image in the case of Rosenlundsverket - Lu, Yongting (My University, 2024)
Industrial buildings are crucial to cities as they not only reflect the historical development, but also serve as monuments which create historical recognition and identification. However, as they are no longer adapted to current requirements, they will end up being demolished or abandoned as there is no need for industrial production. There will be a discern change in their roles which could lead to the vanishing of their image into the development of the city. This thesis focuses on the historic power plant Rosenlundsverket, Gothenburg, Sweden. which will be shut down by 2023. Although its future is still indeterminate, it is expected that the role of Rosenlundsverket in the city will change. Nowadays, Rosenlundsverket is facing a perception crisis. How to intervene such an industrial building so that its function is transformed while still maintaining the original image? Based on The Image of the City, which suggest that people’s perception of space is intermittent, fragmented, and subjective, this project introduces the concept of perception image. The strategy adopted in this project consists of three parts. The street photos of the target building are first obtained through site visit and presented on overhead film. Utilizing overhead film’s characteristic that allows simultaneous display of images from different layers when overlaid, the photos are collaged to visualize the perception image. Perception image together with Aemulatio referred in Adaptive Reuse of Built Heritage are applied at the end. A strategy that let the new design take on the form of the original design instead of separating them as the traditional intervention would perform can aim the industrial building be adapted to the change of its role. The project is based on the assumption that “Rosenlundsverket will be transformed into a public building”. By repurposing the roof, a forecourt is added to the original power plant. The new design will be presented in its original form and blur the separation between the old and new parts of the building, Rosenlundsverket will be therefore transformed into a public building while still maintaining its original perception image.
Keywords: adaptive reuse, industrial architecture, perception image, Aemulatio